Account in "Death on the Nile" Movie (A Discourse Analysis) - Fina Amalia; Sri Wulandari (ELITE: Journal of English Language and Literature, 2023)
This research discusses the aspects of action that contain accounts in Death on the Nile movie, based on the theory of Scott and Lyman (1968) on the aspect of excuses and justification. The objective of this research is to describe the types of accounts in Death on the Nile movie. The researcher used a descriptive qualitative research method. The data sources in this research are divided into two categories, namely movies as primary data and audiovisual as secondary data. Data collection was carried out by downloading movies, watching movies, reading intensively, and selecting data based on the communicative action model. The data was analyzed by presenting, describing, interpreting, and concluding data to answer the research question from this research. The result of the research shows that there are 14 data accounts in Death on the Nile movie. This account occurs because it was created by several characters in the movie who provide excuses and justifications to avoid being accused of the murder incident of a wealthy woman named Linnet. Findings, the researcher found that all justifications are excuses, but not all excuses are justifications. In addition, the justification aspect is more dominant used to justify bad behavior, in the excuses aspect the type of appeal to defeasibility can be used to kill the victim, the appeal to accident aspect is used to make unexpected events, and the appeal to biological aspect is the last aspect that causes behavior. There is no scapegoating aspect in this movie.